Catalytic o-methylation of phenols and its application in converting crude phenols in a low-temperature coal tar to mesitol and durenol. (15th March 2021) - Gao, Hua-Shuai; Zong, Zhi-Min; Teng, Dao-Guang; Li, Jia-Hao; Wei, Xian-Yong; Guo, Qing-Jie; Zhao, Tian-Sheng; Bai, Hong-Cun; Kang, Yv-Hong
Graphical abstract: Complex CPs extracted from a LTCT were methylated to mesitol and durenol. Highlights: Ni/Fe2 O3 specifically catalyzes the alkylation of arenols to ortho -alkylarenols. CPs enriched from LTCT were successfully methylated to mesitol and durenol. Pure mesitol and durenol were isolated from the methylated CPs by elution. Abstract: The alkylation of phenols is an effective method for synthesizing alkylphenols as important chemicals and key building blocks. Herein, we investigated the methylation of phenols over Ni/Fe2 O3 as the catalyst with CH3 OH as methylating agent. The catalyst was characterized by laser ablation inductively coupled plasma mass spectrometry, BET surface area, transmission electron microscopy, NH3 -temperature-programmed desorption, X-ray diffraction, and X-ray photoelectron spectroscopy. The effects of catalyst composition and feed, reaction temperature and time, and recycling times of the catalyst on the o -methylation were systematically examined. As a result, only o -xylenols were detected and their relative contents increase with time under the optimized conditions. The methylation was also used to convert crude phenols extracted from a low-temperature coal tar to value-added chemicals, and consequently mesitol and durenol were produced in total yields up to 99%. Pure mesitol and durenol were obtained after elution and their structures are confirmed by multiple analyses.